Metode Musyafahah Untuk Meningkatkan Kemampuan Membaca Al-Qur’an Siswa SMP-IT As-Salam Ambon - Husen Muhammad; Nur Khozin (Al-Riwayah : Jurnal Kependidikan, 2022)
Abstract: The purpose of this study was to determine the increase in the ability to read the Koran for SMP-IT As-Salam Ambon students using the deliberation method. This research is Classroom Action Research (CAR). The results showed that in the first cycle of 31 students it was found that the qualification score was "very good" as much as one student with a frequency of 3.23%, in the qualification score "good" as many as three students with a frequency of 9.68%, in the qualification value " sufficient" there were five students with a frequency of 16.13%, and in the qualification score "low" there were 11 students with a frequency of 35.48%. Meanwhile, there were 11 students who received a "failed" score with a frequency of 35.48%. In the second cycle of 31 students who had a "very good" grade qualification, there were eight students with a frequency of 25.81%, while those in the "good" qualification score were 21 students with a frequency of 67.74%, and in the "enough" grade qualification only three students remained with a frequency of 6.45%. Then this musyafahah method can be applied to improve students' ability to read the Qur'an.